PENGARUH SENAM HAMIL TERHADAP LAMA KALA I PERSALINAN DI PUSKESMAS CEMPAKA PUTIH - Illa Arinta; Sylvina Rahmawati; Indah Nur Imamah (Husada Mahakam, 2022)
Pregnancy exercise is one of the activities in health services during pregnancy (prenatal care) that will facilitate the process of normal pregnancy or childbirth. The purpose of the study was to determine the effect of pregnant exercise on the duration of the first stage of labor at the Cempaka Putih District Health Center. The research design used was quantitative by using a cross sectional approach, with a sample of 33 mothers giving birth. The instrument used is a register. There is a significant relationship between gymnastics and the period of labor. The results of the study revealed that out of 33 pregnant women who took part in pregnancy exercises routinely as many as 28 respondents with a percentage of 14.76%, while those who did not routinely take part in pregnancy exercise were 5 respondents with a percentage of 15.2%. Respondents who follow gymnastics routinely with the duration of the old labor as much as 69.7%, while the mothers who follow the routine gymnastics with the period of quick labor 30.3%. There is a significant relationship between gymnastics and the period of labor.